Perancangan Usulan Tata Letak Produksi Usaha Kecil Menengah Bata Merah Wiyono - Pratiwi, Filda Yuriski; Loyda Tarigan, Elsya Paskaria (Fakultas Teknik UMRI, 2023)
This study aims to provide suggestions for improvements to the layout of the Wiyono Red Brick Small and Medium Enterprises so that a more optimal layout is obtained in terms of track distance, simpler material flow, material handling costs, and designing rest areas for workers in the Wiyono Red Brick Small and Medium Enterprises. The Wiyono Red Brick Small and Medium Enterprises are required to make the track distance shorter and material handling costs cheaper. The necessary data was collected by conducting interviews with business owners and making direct observations at the Wiyono Red Brick Small and Medium Enterprises. This study used the Computerized Relative Allocation of Facilities Techniques (CRAFT) method. The results of the analysis using the CRAFT method show that the proposed layout has an alternative OMH layout of Rp.1,464,676.5, while the initial layout is Rp. 2,831,368.1, resulting in a difference of Rp. 1,366,691.6. The total distance of the initial layout is 269,654 m, while the alternative distance is 139,493 m with a difference of 130,161 m. From the results of the comparison, it is found that the difference between the initial layout and the alternative layout is so large that it is necessary to apply the alternative layout to make production more optimal.